Intersubjective intentionality, moral consciousness, and media ecology. Issue 4 (2nd October 2017) - Bogaczyk, Jeffrey
ABSTRACT: In our current historical moment, marked by increasing technological mediation of human communication, this essay investigates the relationship between, and effects of, technological mediation on intersubjective intentionality and moral consciousness. Beginning with an explication of the phenomenological concept of intersubjective intentionality as a key component in the structure of moral consciousness, this essay then investigates how media ecology can provide insight to the effects of technological mediation and digital communication technologies on our intersubjective relationships and our moral experiences.